Simulation model development and experimental validation of a PFC converter - Martins, Antonio Pina; Morais, Vítor A. (Institute of Advanced Engineering and Science, 2024)
The most common interface to the electric grid of small power loads, which is based on a diode bridge followed by a bulk capacitor, generates a large number of low-frequency harmonics in the input current. To comply with the IEC 61000-3-2 and IEEE 519 standards it is needed to optimize the interface in terms of current harmonics and the topology composed by a diode bridge and a DC/DC boost converter operating in the critical conduction mode is one having a greater number of comparative advantages. There is a large number of controllers in the market but also a lack of the associated simulation models exists. This paper focuses on the development, validation and testing of a simulation model that mimics an existing integrated circuit and allows for an accurate prediction of the real behavior of the complete converter. The experimental results validate the model with high fidelity and confirm the added value of the topology and control method applied either in transient and steady-state operation.